Computer modeling of digestive processes in the alimentary tract and their physiological regulation mechanisms: closing the gap between digestion models and in vivo behavior - van Aken, George A. (Frontiers in Nutrition, 2024)
Introduction A model has been developed for in silico simulation of digestion and its physiological feedback mechanisms. Methods The model is based on known physiology described in the literature and is able to describe the complexity of many simultaneous processes related to food digestion. Results Despite the early stage of development of the model, it already encompasses a large number of processes that occur simultaneously, enabling the prediction of a large number of post-prandial physiological markers, which can be highly functional in combination with in vitro, organ-on-a-chip and digital twin models purposed to measure the physiological properties of organs and to predict the effect of adjusted food composition in normal and diseased states. Discussion Input from and collaboration between science fileds is needed to further develop and refine the model and to connect with in vitro, in vivo, and ex vivo (organ-on-a-chip) models.